Implications of Constitutional Court Decision Nunber 69/PUU-XIII/2015 on The Status of Marriage Agreements and The Regulation of Joint Property Separation - Bertha Salmania Putri; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
This research is motivated by the increasing number of divorce cases involving disputes over joint property acquired during marriage. Additionally, many couples bring assets into the marriage, prompting some to enter into a marriage agreement that separates their assets. This study aims to examine: (1) the legal standing of marriage agreements made before and during marriage based on Constitutional Court Decision Number 69/PUU-XIII/2015, and (2) the implications of this decision on marriage agreements made during marriage. The research method used is normative juridical. The study aims to provide a clear and concise overview of the legal force of marriage agreements executed after marriage. The results indicate that (1) marriage agreements made after marriage carry the same legal force as court rulings and are legally recognized under the Constitutional Court Decision, and (2) the decision introduces new provisions allowing marriage agreements to be made during marriage—deviating from previous provisions under Law Number 1 of 1974 on Marriage, which only allowed agreements to be made before marriage.